A study into the effectiveness of budgeting and budgetary control in sourcing funds in Nongovernmental organisations: a case study of Norwegian Refugee Council (NRC) - Mlambo, Meblyn (Midlands State University, 2017)
Ineffective budgeting and budgetary controls in nonprofit organisations have impacted negatively in sourcing funds to carry out humanitarian Aid. Ineffective budgetary controls in non profit organisations has also affected the implementations of projects and has left most vulnerable persons helpless as the organisations fail to secure more funding. The purpose of this research was to study the effectiveness of budgeting and budgetary control in sourcing funds in nonprofit organizations. The research used a descriptive research design on a case study of Norwegian Refugee Council. Questionnaires were administered and the interviews were conducted with management personnel, secondary data was obtained from the internal records of the organization. The research findings indicated that budgets and budgetary control are time consuming and are presented as fixed. The findings also indicated that budgets and budgetary control also attracts more funding from donors as they increase donor transparency and accountability. The study recommends that the organization should establish a budget committee so that it facilitates all the budgeting processes in the organization for instance, setting up of budget manuals and budget periods. It also recommends that the organization should adopt an effective or sound budgetary control system in order to secure funding from its already existing and new donors.